2017
DOI: 10.1002/cta.2328
|View full text |Cite
|
Sign up to set email alerts
|

Realization of a transfer function as a passive two‐port RC ladder network with a specified gain

Abstract: Summary This paper is concerned with the realization problem for a class of high‐pass as well as low‐pass transfer functions as a two‐port RC ladder network with a specified gain, which requires that the actual gain of the realization configuration is equal to the gain of the given transfer function. From a cascade realization approach, it is shown that any transfer function belonging to the class under investigation can be realized as a two‐port RC ladder network with any specified gain in a continuous interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…According to (30), it can be concluded that Y c ðsÞ is a rational positive-real odd function of s and all zeros and poles of Y c ðsÞ are on the imaginary axis. Thus, Y c ðsÞ of (30) satisfies lemma 1, and Y c ðsÞ of (30) can be expressed as…”
Section: Numerical Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…According to (30), it can be concluded that Y c ðsÞ is a rational positive-real odd function of s and all zeros and poles of Y c ðsÞ are on the imaginary axis. Thus, Y c ðsÞ of (30) satisfies lemma 1, and Y c ðsÞ of (30) can be expressed as…”
Section: Numerical Examplesmentioning
confidence: 99%
“…Applications of the inerter to vehicle suspension, 28 motorcycle steering control, and vibration absorption have been identified with the performance advantages demonstrated. 29,30 The need for a renewed attempt on the same subject and its fundamental connection to system theory has also been highlighted by Kalman. 31 Biquadratic admittance is one of the most important topics in passive network synthesis, which can provide guidance for the development of more general situations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the relevant literature, especially in the d\omain of automation and control, different approaches for dynamic object identification are presented. [1][2][3][4][5][6][7][8][9][10][11][12][13] Many methods have been elaborated and are recommended for use in electrical and electronic applications. 1,2,[11][12][13] Typically, the system is presented as a passive multistage circuit containing resistances, capacitors and inductances.…”
Section: Introductionmentioning
confidence: 99%
“…Derivation of resistance R n ðA x 1 ; A x 2 ÞCombining equations (15)-(17),(19),(21),(23) and(27), the solution of X k i…”
mentioning
confidence: 99%